Pengaruh Program Pengungkapan Sukarela (Tax Amnesty Jilid Ii) Dan Kualitas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Pada Kpp Pratama Jakarta Menteng Satu) - Daryanto Hesti Wibowo; Septia Imelda (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The purpose of this study was to analyze the effect of the Voluntary Disclosure Program (Tax Amnesty Volume II) and the Quality of Fiscal Services on Individual Taxpayer Compliance. The method used in this study was a quantitative method with 100 taxpayer respondents registered at Menteng Small Tax Office One Jakarta through a random sampling method. The conclusions made in this study are that the Voluntary Disclosure Program (Tax Amnesty Volume II) and the Quality of Fiscal Services have a positive and significant effect on Individual Taxpayer Compliance at Menteng Small Tax Office One Jakarta.